Irrigation Schedule of Rice Based on CROPWAT Model in Southern Central Yunnan - DUAN Qicai; WANG Shupeng; ZHANG Lei; LUO Yingpei; QI Na (Renmin Zhujiang)
This study is conducted to further review the rationality of the standard for rice irrigation quotas in Jianshui of southern central Yunnan.On the basis of the observation data of Jianshui Meteorological Station from 1958 to 2013 and the rice-season test results of irrigation test sites in Jianshui from 2016 to 2018,the crop and soil parameters in the CROPWAT model are calibrated,and the processes of water in the rice soaking stage and irrigation amount in the prime field stage are simulated.With frequency arrangement results of irrigation amount in the whole growth stage,the rice irrigation schedule is drafted by the typical-year method.The results indicate that under the irrigation probability (P) of P=50%,P=75%,and P=90%,the irrigation quota of Jianshui rice in the whole growth stage is 510.1,591.1,and 651.2 mm,respectively,including the quota for the rice soaking stage of 185.3,209.2,and 213.9 mm,as well as the quota for the prime field stage of 324.8,381.9,and 437.3 mm,respectively.The irrigation frequency in the prime field stage is 8,9,and 10 times,respectively,and the irrigation quota is between 20.3 to 46.7 mm.The standard for rice irrigation quotas in Jianshui of southern central Yunnan is between 240.0 to 255.0 mm in the rice soaking stage,and under the conditions of P=50%,P=75%,and P=90%,the rice irrigation quota in the prime field stage is 427.5~435.0,487.5~502.5,540.0~562.5 mm,respectively.The current standard for rice irrigation quotas is basically reasonable,but from the viewpoint of water conservation and protection,there is still some water-saving space for rice irrigation.